2017
DOI: 10.1002/pssa.201600390
|View full text |Cite
|
Sign up to set email alerts
|

Size effect of the silicon carbide Young's modulus

Abstract: A self-consistent method is used for the determination of the residual stress and the effective Young's modulus of thin 3C-SiC (111) grown on Si(111), and 3C-SiC(100) grown on Si(100). The developed method allows for the accurate determination of the stress and mechanical properties in a wide range of residual stress, only by a set of cantilevers and doubly clamped beams. The resulting thickness dependence of the effective Young's modulus is investigated and compared with different elasticity and surface relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In Figure 15 and Figure 16 , we compared our results with other data reported in previous papers [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 85%
“…In Figure 15 and Figure 16 , we compared our results with other data reported in previous papers [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 85%
“…As a consequence, γ n is assumed to be constant for the present analysis. Recent investigations of 3C-SiC (111) bridges [43] showed that γ n tends to be constant even for higher strains. As this finding is not directly applicable to ScAlN bridges, separate studies for the present material system are needed.…”
Section: Modal Analysismentioning
confidence: 99%
“…The temporal duration of a switch's release is observed to exhibit an elongation ranging from 5% to 13% when compared to switches based on planar cantilever configurations. The utilization of RF MEMS switches has been identified across various disciplines (Nakajima et al, 2017;Shen et al, 2021;Kurmendra and Kumar, 2021a;Riverola et al, 2016a;Hähnlein et al, 2017). Casimir's force increases as the square root of the inverse of the square of the gap (Koul and Dey, 2022;Duan and Rach, 2013;Tsai and Li, 2022).…”
Section: Introductionmentioning
confidence: 99%